RANCANG BANGUN CRM (CUSTOMER RELATIONSHIP MANAGEMENT) KOPERASI SERBA USAHA (KSU) MINA SEJAHTERA KENDAL BERBASIS WEB (Information Technology and Telematics, 2016)
Abstract -The purpose of this research is to build crm ( customer relationship management )in cbc ( completelybusiness cooperative )mina sejahtera located in kendal, precisely in jl.Jodipati no. 2 purin ( purwokerto indah) kendal city a zip code 51353.Of problems that emerged in the cooperative is not be used information technology, so information about who there still can be maximallywell. This research uses the method the literature study and observation.Data in a can of archives cooperatives, interview with managers cooperatives, or many data cooperatives that are able to support research as profile cooperatives, vision the mission and the structure of the organization.While system in cbc ( completelybusiness cooperative )mina sejahtera this developed by the use of system prototyping by using programming language php and a database mysql. The result of this research is the information in cooperatives can access via web cbc mina sejahtera , common user can also call their cooperatives online through form that has been in provide on the web , as well as those officers will obtain a sms a reminder the schedule back their autorespond and text messages. Keywords:Customer Relationship Management, Minasejahtera Cooperative, PrototypingMethod, PHP, MySQL SMS Gateway,  SMS Reminder, SMS Autorespond.